Are Forces Invited From A Foreign State Liable To The Laws Of The Host State? - Marasinghe, Lakshman (Journal of Malaysian and Comparative Law, 1989)
As early as 1826 Great Britain despatched her forces at the request of the Portugese government to put down a rebellion caused by the Portugese nationalist - Don Migul.